Biomechanical changes in the pharynx and upper esophageal sphincter after modified balloon dilatation in brainstem stroke patients with dysphagia. Issue 12 (14th August 2013) - Lan, Y.; Xu, G.; Dou, Z.; Wan, G.; Yu, F.; Lin, T.
Abstract Background Few studies have investigated the biomechanical changes in the upper esophageal sphincter (UES) and pharyngeal function after successful dilatation therapy for dysphagia. Using high‐resolution manometry (HRM), we examined the biomechanical properties of swallowing in brainstem stroke patients with dysphagia following modified balloon dilation therapy. Methods 30 brainstem stroke patients with dysphagia were included. Patients in the experimental group received 3 weeks of modified balloon dilatation treatment and regular dysphagia therapy. Patients in the control group received 3 weeks of regular dysphagia therapy only. Efficacy of treatment was evaluated before and following intervention. Functional oral intake was measured using the Functional Oral Intake Scale (FOIS). Pharyngeal maximum pressures and duration, UES residual pressure and duration during swallowing were measured using HRM. Key Results In the experimental group, the feeding tube was able to be removed in 12 of 15 patients, vs 2 of 15 patients in the control group. The experimental group had 4‐point median improvement, while control groups only had 1‐point improvement in FOIS scores. In the experimental group, posttreatment UES relaxation and pharyngeal propulsion were both significantly improved for the three materials (p < 0.05) and UES resting pressure approximated normal. In the control group, pharyngeal propulsion was improved for water and thick liquids (p < 0.05) but not for paste material; there was no improvement in posttreatment UES relaxation for all three materials (p > 0.05). Conclusions & Inferences Dysphagia therapy with modified dilatation improved UES relaxation, strengthened pharyngeal propulsion, restored UES resting pressure and improved functional oral intake to a greater extent than regular therapy alone.